Kidney Disease Profiles Among Adolescents In Indonesia - Partini Pudjiastuti Trihono; Lia Rhodia; Mulya Rahma Karyanti (Interna Publishing, 2019)
Background: Each kidney injury may develop into chronic kidney disease (CKD) and end stage renal disease (ESRD) that associates with high mortality and socio-economic burden. There is limited data about clinical characteristics of children having CKD in developing countries, espesially in Indonesia. Objective: To describe clinical profiles and characteristics of kidney diseases in adolescents aged 15-18 years. Methods: This study was a cross-sectional study which used data from National Basic Health Survey (Riskesdas) 2013. There were 2 data groups. The first data group included questionnaires about history of kidney stone disease, hypertension, chronic renal failure, antihypertension administration, and blood pressure measurement. The second data group included subsamples of the first group which had laboratory test results, i.e. hemoglobin and serum creatinine levels. All of the data were classified by nutritional status, estimated glomerulofiltration rate (eGFR), blood pressure classification, and hemoglobin level. Results: Among 52,454 adolescents in the first data group, 20,537 (39%) had kidney diseases with female predominance and good nutritional status. Other findings found were history of kidney stone disease (0.2%), chronic renal failure (0.1%), history of hypertension (0.6%), antihypertensive agents consumption (0.1%). Prehypertension and hypertension were found in 51% and 48.3% of adolescents, respectively. Adolescents with decreased eGFR were accounted for 1.4%. Conclusion: The proportion of prehypertension and hypertension in adolescents aged 15-18 years in Indonesia is high. Hence, routine blood pressure measurement is important for early detection and prevention of kidney disease progression. Keywords: adolescent, kidney disease, hypertension, prehypertension, National Basic Health Survey